Characterization and extraction of the synaptic apposition surface for synaptic geometry analysis - Morales, Juan; Rodriguez, Angel; Rodriguez, José-Rodrigo; DeFelipe, Javier; Merchan-Perez, Angel (Frontiers in Neuroanatomy, 2013)
Geometrical features of chemical synapses are relevant to their function. Two critical components of the synaptic junction are the active zone and the postsynaptic density, as they are related to the probability of synaptic release and the number of postsynaptic receptors, respectively. Morphological studies of these structures are greatly facilitated by the use of recent electron microscopy techniques, such as combined focused ion beam milling and scanning electron microscopy (FIB/SEM), and software tools that permit reconstruction of large numbers of synapses in three dimensions. Since the active zone and the postsynaptic density are in close apposition and have a similar surface area, they can be represented by a single surface — the synaptic apposition surface (SAS). We have developed an efficient computational technique to automatically extract this surface from synaptic junctions that have previously been three-dimensionally reconstructed from actual tissue samples imaged by automated FIB/SEM. Given its relationship with the release probability and the number of postsynaptic receptors, the surface area of the SAS is a functionally relevant measure of the size of a synapse that can complement other geometrical features like the volume of the reconstructed synaptic junction, the equivalent ellipsoid size and the Feret’s diameter.